Artificial Intelligence and Qur’anic Interpretation: A Critical Comparative Study of ChatGPT and Classical Tafsir - Muhammad Andrean; Mardian Idris Harahap (Jurnal test, 2025)
This study aims to evaluate the accuracy and feasibility of using ChatGPT in interpreting the Qur’an by comparing its interpretations with those of classical tafsir. The research employed a qualitative comparative analytical design using a library-based approach. Three Qur’anic verses, namely Surah Yunus: 26, Āli ‘Imran: 130, and Yunus: 89, were analyzed across three dimensions: linguistic accuracy, contextual understanding, and depth of interpretation. The results indicate that while ChatGPT provides coherent and accessible explanations, it lacks the methodological rigor and contextual depth characteristic of traditional tafsir. This study provides an initial mapping of the strengths and limitations of artificial intelligence in Qur’anic interpretation and emphasizes the need to develop an integrative methodological framework to ensure that AI-based tafsir remains consistent with scholarly and Sharia principles. Future research is recommended to explore other AI models and to develop tafsir-based filters to enhance interpretive validity.